Burden and trends of dietary iron deficiency in the Middle East and North Africa region, 1990–2021 - Safiri, Saeid; Amiri, Fatemeh; Karamzad, Nahid; Sullman, Mark J. M.; Kolahi, Ali-Asghar; Abdollahi, Morteza (Frontiers in Nutrition, 2025)
ObjectiveTo assess the burden of dietary iron deficiency in the Middle East and North Africa (MENA) region, focusing on prevalence and years lived with disability (YLD) in 2021 and their changes since 1990.MethodsData from the Global Burden of Disease (GBD) 2021 study were utilised to report counts and age-standardised rates for prevalence and YLD related to dietary iron deficiency. All estimates were accompanied by 95% uncertainty intervals (UIs).ResultsIn 2021, the age-standardised prevalence of dietary iron deficiency in the MENA region was 14368.2 per 100,000, representing a 26% decline since 1990. The highest age-standardised prevalence rates were observed in Yemen (30146.5), Sudan (19296.9), and Morocco (15,303) per 100,000 population. Prevalence was notably highest among children under 5 years old and women of reproductive age, with a gradual decline in older age groups. The greatest reductions in prevalence were seen among older age groups, indicating an age-related downward trend from 1990 to 2021.ConclusionDespite some improvements, dietary iron deficiency remains a significant public health concern in the MENA region, particularly in countries with lower socio-demographic indices (SDI). Targeted interventions are essential, especially for vulnerable groups such as children and women.